Comparative study of descendent colon rupture resistance considering traction force of rupture and total energy of rupture in rats - Wu,Feng Chung (2006)
PURPOSE: To compare total energy of rupture and traction force of rupture tests within a rupture resistance study of descendent colon of rats. METHODS: Twelve descendent colon segments of rats were considered to perform the study. For each one of the specimens, total energy of rupture and traction force of rupture necessary to promote colic wall burst were evaluated through the biomechanical total energy of rupture test using the Biomechanical Data Acquisition and Analysis System, version 2.0. Average, standard deviation, standard error of average and coefficient of variation were considered for analysis of results. RESULTS: Traction force of rupture average, standard deviation, standard error of average and coefficient of variation were 380.05 gf, 98.74, 28.5 e 25.98%, respectively while total energy of rupture presented average of 244.85 gf, standard deviation of 57.76, standard error of average of 16.67 and coefficient of variation of 23.59. CONCLUSION: Although, total energy of rupture considered a larger number of attributes to its calculation related to non-linear viscoelastic materials, such as colic wall, it presented a smaller coefficient of variation when compared to traction force of rupture, thus demonstrating to constitute a possible parameter to analyze intestinal resistance of rats.